An assessment of climate change impacts on the tropical forests of Central America using the Holdridge Life Zone (HLZ) land classification system - Khatun, Kaysara; Imbach, Pablo A.; Zamora, Juan Carlos (2015)
Ecological models have predicted shifts in forest biomes, yet there have been very few studies that have looked at the implications on carbon stocks due to these shifts. Carbon is closely correlated to biomass and constitutes an important characteristic of the forest ecosystem. It has implications for conservation and land use practices, especially for climate change mitigation strategies currently under discussion, such as the Reduced Emissions from Deforestation and Forest Degradation (REDD). This study couples the Holdridge Life Zone (HLZ) classification with the ECHAM5 model, to evaluate the impacts of climate change using the Special Report on Emissions Scenarios (SRES) A2, A1B and B1 for the Central American region. We utilize methodologies which combine biophysical variables with model output to assess the impacts on carbon stocks for two time periods, 2000 and 2100. Results show that overall the tropical category of the HLZ classification gains area as a consequence of one type of HLZ shifting to another forest type. In many cases the shifts lead to some categories of HLZ being lost in their entirety. Elevation-associated life zones are particularly vulnerable to future climatic changes. A strong point of our approach is that differences between disaggregate regional and aggregate country levels can be compared. We suggest that a critical focus of conservation and management efforts should be concentrated on where vulnerable biomes are at most risk, i.e., biomes that shift and/or reduce fall under the vulnerable category.